2022
DOI: 10.3390/molecules27196234
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Regulation of Thromboxane A2 Signaling in Cancer-Trojan Horses and Misdirection

Abstract: Over the last two decades, there has been an increasing awareness of the role of eicosanoids in the development and progression of several types of cancer, including breast, prostate, lung, and colorectal cancers. Several processes involved in cancer development, such as cell growth, migration, and angiogenesis, are regulated by the arachidonic acid derivative thromboxane A2 (TXA2). Higher levels of circulating TXA2 are observed in patients with multiple cancers, and this is accompanied by overexpression of TX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 163 publications
0
9
0
Order By: Relevance
“…MiR-125b-1 is produced by the long non-coding RNA (lncRNA) MIR100HG, its overexpression has been associated with oncogenic events, including abnormalities such as chromosomal translocation (t (2; 11) (p21; q32)). However, there is currently no evidence linking this miRNA to the development of NSCLC ( Wang et al, 2020 ; Ashton et al, 2022 ). Whereas, it has been reported miR-125b-2 is generated from the miRNA cluster miR-99a/let-7c/miR-125b-2, located on chromosome 21.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-125b-1 is produced by the long non-coding RNA (lncRNA) MIR100HG, its overexpression has been associated with oncogenic events, including abnormalities such as chromosomal translocation (t (2; 11) (p21; q32)). However, there is currently no evidence linking this miRNA to the development of NSCLC ( Wang et al, 2020 ; Ashton et al, 2022 ). Whereas, it has been reported miR-125b-2 is generated from the miRNA cluster miR-99a/let-7c/miR-125b-2, located on chromosome 21.…”
Section: Resultsmentioning
confidence: 99%
“…In both, LUAD and LUSC, it has been demonstrated that LRP1 decreases its expression compared to healthy tissues, while in other tissues like brain cancers its expression increases, suggesting that LRP1 plays a role in glioma growth ( Lopes et al, 1994 ). Thromboxane A synthase 1 (TBXAS1) is known to play functional roles in processes such as neoplastic transformation, including cell motility and invasion, proliferation, and therapeutic resistance ( Ashton et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the PGD2‐CRTH2 axis has been implicated in immune suppression and the establishment of a tumor‐supportive microenvironment [ 102 ]. Thromboxane A2 (TXA2), another metabolite of AA through the COX pathway [ 91 , 126 ], can exert immunosuppressive effects, thereby facilitating tumor growth as well [ 127 ]. Inhibitory effects of TXA2 on CD8 + T cells and DCs have also been noted in studies using melanoma and breast cancer allografts [ 128 ].…”
Section: The Crosstalk Between Ferroptosis and Anti‐tumor Immunity In...mentioning
confidence: 99%
“…The short-lived TXA 2 can then act on the thromboxane receptor (TBXA 2 R, TP) which exists in two isoforms (α and β). Although TXA 2 appears to be of minor importance in the maintenance of renal functioning under physiological circumstances [ 161 ], an overexpression of TXA 2 S mRNA has been reported in renal cancer cells [ 162 ]. The relevance of this observation for RCC remains open.…”
Section: Eicosanoids In Renal Cancermentioning
confidence: 99%
“…TBXA 2 R is up-regulated in various tumors, and data from the Cancer Cell Line Encyclopedia show significant up-regulation in renal cancer, although without specification of the type of renal cancer [ 162 ]. Interestingly, a mutation of the β isoform of TBXA 2 R (SNP: rs200445019) was associated with metastatic disease at multiple tissue sites originating from primary renal cancer [ 162 ]. Another study shows that the β isoform is highly expressed in RCC cell lines which suggests the TBXA 2 R-β a candidate for further exploration [ 163 ].…”
Section: Eicosanoids In Renal Cancermentioning
confidence: 99%